A STEP BY STEP DESIGN GUIDE FOR A SOLAR WATER HEATING SYSTEM CONSIDERING THERMAL LOSSES - Barbosa, R. R.; Carvalho, M. (Revista de Engenharia Térmica, 2019)
A clear and direct guide for the design of a solar heating system is presented herein, focused on industrial applications. This guide focuses on the design of solar water heating systems for nonresidential applications. The importance of considering climatic conditions throughout the year is highlighted herein, along with reliable solar radiation data. Solar heating water systems are essential for the diversification of the Brazilian energy matrix and rationalization of the energy resources available. The system is initially dimensioned without the consideration of losses. Then, the required procedure to calculate thermal losses is described, and it is verified that the main losses occur in solar collectors and storage. After careful consideration of the hot water consumption profile and the results obtained in the calculation of the main thermal losses, the storage volume was doubled to guarantee the satisfaction of energy demands.